AMC loaded folded dipole with heart‐shaped radiation pattern. Issue 18 (1st September 2018) - Mostafa, M.M.; Abuelfadl, T.M.; Safwat, A.M.E.
Abstract : This Letter presents a novel pseudo‐omnidirectional antenna that is appropriate for wide beam applications, e.g. handheld devices, along with a reduced back radiation that suits wearable applications as well. The design consists of a horizontal omnidirectional antenna placed on a proposed artificial magnetic conductor (AMC) surface that enhances the gain in the broadside direction, reduces the back radiation, and enables good radiation in the side directions. A 5 GHz folded dipole on a 2 × 2 AMC array surface is designed and characterised. Simulations and measurements, which are in a very good agreement, show that the radiation has a heart‐shaped pattern, with a front to back ratio of >13 dB, a front to side ratio of <2.5 dB, and a half‐power beam width of >230°.